Comparison of clinicopathological features and long-term prognosis between mixed predominantly differentiated-type and pure differentiated-type early gastric cancer - Okagawa, Yutaka (BMC Cancer, 2021)
BACKGROUND: Recent studies have shown that mixed predominantly differentiated-type (MD) early gastric cancer (EGC) might have more malignant potential than pure differentiated-type (PD) EGC. However, no study has analyzed all differentiated-type EGC cases treated endoscopically and surgically. This study aimed to compare the differences in clinicopathological features and long-term prognosis between MD- and PD-EGC. METHODS: We evaluated all patients with differentiated-type EGCs who were treated endoscopically and surgically in our hospital between January 2010 and October 2014. The clinicopathological features and long-term prognosis of MD-EGC were compared with those of PD-EGC. RESULTS: A total of 459 patients with 459 lesions were evaluated in this study; of them, 409 (89.1%) and 50 (10.9%) were classified into the PD and MD groups, respectively. Submucosal invasion was found in 96 (23.5%) patients of the PD group and in 33 (66.0%) patients of the MD group (p < 0.01). The rates of positive lymphatic and vascular invasion and ulceration were significantly higher in the MD group than in the PD group (p < 0.01). The proportion of patients with lymph node metastasis was also significantly higher in the MD group than in the PD group (5 (10%) vs 6 (1.5%), p < 0.01). The 5-year overall and EGC-specific survival rates in the PD group were 88.3 and 99.5%, respectively, while they were 94.0 and 98.0% in the MD group, respectively. CONCLUSIONS: MD-EGC has more malignant potential than PD-EGC. However, the long-term prognosis of MD-EGC is good and is not significantly different from that of PD-EGC when treated appropriately.